2010
DOI: 10.2478/v10044-008-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of facial preferences in boys at early adolescence

Abstract: Research on facial attractiveness has become very popular in past few decades and the psychoevolutionary perspective has recently gained a good measure of scientific currency. This perspective assumes that many of the criteria for facial preferences have been molded by natural selection so that the pursuit of and contact with individuals perceived as attractive is beneficial for one's reproductive success [Symons 1995, Gangestad & Scheyd 2005, Rhodes 2006]. It is no wonder then that facial preferences are, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For instance, earlier first menses is associated with earlier first coitus (e.g., Downing & Bellis, 2009;Udry 1979) and given the sex difference in age of puberty those early relationships are likely to be with older males. Related to this, Kościński (2010) found that boys' sexual experience predicted similar patterns of face preferences as their pubertal development, highlighting the impact experience may have.…”
Section: Activation Of Preferences Across Childhood and Pubertymentioning
confidence: 62%
See 2 more Smart Citations
“…For instance, earlier first menses is associated with earlier first coitus (e.g., Downing & Bellis, 2009;Udry 1979) and given the sex difference in age of puberty those early relationships are likely to be with older males. Related to this, Kościński (2010) found that boys' sexual experience predicted similar patterns of face preferences as their pubertal development, highlighting the impact experience may have.…”
Section: Activation Of Preferences Across Childhood and Pubertymentioning
confidence: 62%
“…In fact, although overall means for femininity and symmetry preferences increased with age, preferences for averageness decreased. Correspondingly, Kościński (2010Kościński ( , 2011Kościński ( , 2013 found a similar pattern of means in strength of preference for skin health in girls and boys aged between 11 and 14 years. In the only longitudinal data on facial preferences we are aware of, Saxton et al (2011) were unable to document any clear changes in adolescent's facial preferences over a 1 year period, although in a later study on voices it was observed that 11-and 13-year olds showed a drop in voice pitch preference over a 9-12 month period (Saxton et al, 2013; see also Saxton et al, 2009 for similar cross-sectional patterns in voice pitch preference).…”
Section: Activation Of Preferences Across Childhood and Pubertymentioning
confidence: 79%
See 1 more Smart Citation